PENGARUH STRUKTUR KEPEMILIKAN DAN POLITICAL VISIBILITY PADA LUAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Kusumadewi, Ni Made Yuli; Suaryana, I Gst Ngr Agung (E-Jurnal Akuntansi; Vol 9 No 1 (2014), 2014)
This research aims to test influence of ownership structure (managerial ownership, institutional ownership) and political visibility in area of corporate social responsibility disclosures. Companies listed in BEI in 2012 was chosen as  location for research. Samples taken used probability sampling method with 82 companies. Multiple regression was used as analysis techniques. The results illustrate a positive effect on institutional ownership is widespread disclosure of corporate social responsibility and a company that has great political visibility reveals corporate social responsibilitity more than companies with political visibility is low. Managerial ownership no effect on broad disclosure of corporate social responsibility.
Keywords: ownership structure, political visibility, disclosure